If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7x + -1 = 4x + -89 Reorder the terms: -1 + -7x = 4x + -89 Reorder the terms: -1 + -7x = -89 + 4x Solving -1 + -7x = -89 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -1 + -7x + -4x = -89 + 4x + -4x Combine like terms: -7x + -4x = -11x -1 + -11x = -89 + 4x + -4x Combine like terms: 4x + -4x = 0 -1 + -11x = -89 + 0 -1 + -11x = -89 Add '1' to each side of the equation. -1 + 1 + -11x = -89 + 1 Combine like terms: -1 + 1 = 0 0 + -11x = -89 + 1 -11x = -89 + 1 Combine like terms: -89 + 1 = -88 -11x = -88 Divide each side by '-11'. x = 8 Simplifying x = 8
| 8b+5-6b=3 | | 2x+12+4x+18=66 | | 8b+12=8+7b+4 | | -40x^2+62x+63=0 | | -4(11a-6)+9(4+2a)=x | | y=10-3(x*2) | | -5y+18=4y | | 20=x-((x*.05)+1) | | 9-(x+6)=4x-7 | | 2x+12v+4x+18=66 | | (2x+8)+(3x+17)=5y+17 | | 2x-60=570 | | 7.5x15x1/2 | | -x=3x+2 | | x=x-(.05x+1) | | 5n+8+6=21 | | 5-104=8(p-8) | | 4w+16=2w+10 | | -(-2+8r)=6-15r | | 9(c+1)=8c-6 | | 4x-2x=570 | | -4.4z+5.9=-4.9z+2.9 | | 120=15/1/2 | | 3(x-1)-2(3x+2)=5(1-x) | | 1+3(-5z-3)=-5(5z+6)+3 | | w-3x-2y+2z=0 | | 4x15x1/2 | | 31y-(-1+10y)=-20 | | -6x=-3x-15 | | t=-16t^2+82t | | 9x-4=2t+3 | | 6y-23=14 |